Development of Encyclopedia on Reproductive System Material for Class XI at Hang Tuah Belawan High School - Pranriska, Iftitah; Manalu, Kartika (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study was undertaken to address the issues identified during preliminary research, which revealed that teachers were still using packaged books and worksheets as their teaching materials. Based on these findings, the researchers became interested in developing teaching materials in the form of encyclopedias. Encyclopedias have the advantage of being both a source of information and a teaching aid. The objective of this study was to develop a valid, practical, and effective encyclopedia on the topic of the reproductive system. The research methodology employed in this study was Research and Development (R&D), utilizing the 4-D development model, which encompasses the stages of define, design, develop, and disseminate. Validity, practicality, and effectiveness instruments were used as research tools, and data analysis was conducted using a Likert scale. The results revealed that the encyclopedia met the criteria for validity (as determined by 92% of teaching material experts and 83% of content experts), practicality (as reported by 95% of teachers and 84% of students), and effectiveness (as demonstrated by an increase in pretest scores from 56.22 to a posttest score of 89, resulting in an N-Gain of 0.75, with a percentage of 75%). Therefore, it can be concluded that the reproductive system encyclopedia is valid, practical, and effective, making it suitable for use in learning activities. The development of this reproductive system encyclopedia has significant implications for the learning process, particularly in terms of adopting a more comprehensive learning approach. The encyclopedia provides extensive and in-depth information, fostering a more holistic learning experience and transforming the role of the teacher into that of a facilitator who assists students in navigating and comprehending information.